Review of Superstructure Calculations in Replacement Projects Wai Poka Bridge, Ambon City - Jimmy Peter Gerit Pudehokang; Hamkah; Godfried Lewakabessy (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This study is motivated by the aging condition of steel truss bridges in Indonesia, particularly the Wai Poka Bridge in Ambon City, which has caused lane narrowing and reduced structural performance. The study aims to analyze the ultimate moment of the bridge superstructure and evaluate the reinforcement design of conventional concrete girders based on SNI 1725:2016. A descriptive quantitative approach was employed. The population consisted of concrete girder elements within the Maluku national road network, while the sample was purposively selected from the critical dimensions of the Wai Poka Bridge. Research instruments included field surveys and design documents, with data analyzed using SNI-based calculations and structural software. The results indicate that the maximum ultimate moment reached 13,611 kNm and the shear force reached 1,620 kN, with required flexural reinforcement of 33D32 and stirrups of 2D13-200 meeting strength, deflection, and ductility criteria. The conclusion shows that the superstructure replacement design is safe, reliable, and economical, and feasible for similar bridge rehabilitation projects